NONDESTRUCTIVE TESTING FOR ARCHAEOLOGY AND CULTURAL HERITAGE A PRACTICAL GUIDE AND NEW PERSPECTIVES - Leucci, Giovanni (Switzerland Springer Nature, 2019)
This textbook provides a general introduction to the most important nondestructive testing (NDT) exploration methods for cultural heritage sites. It highlights the application of NDT exploration methods to archaeology and monumental property. The ability to gauge the extent of an archaeological deposit or the state of preservation of artefacts without resorting to destructive actions is extremely useful in identifying unknown or presumed artefacts, and can help to understand and approach a given site in a targeted manner, both for excavation and restoration operations. This book describes the main physical principles, campaign procedures, and processing and interpretation techniques of NDT, while also introducing a new technique and algorithm for data acquisition and processing. A large section of the book is devoted to actual site applications, and focuses on significant historical-archaeological sites in Italy and Turkey. The book offers an essential reference guide for students and scientists in archaeology, geophysics, architecture, and the engineering disciplines, as well as specialists.
Keywords: Geophysical Instrumentation -- Pompeii -- Sagalassos